Quantum gravity inspired nonlocal gravity model - Amendola, Luca; Burzillà, Nicolò; Nersisyan, Henrik (Arxiv, 2017)
We consider a nonlocal gravity model motivated by nonperturbative Quantum Gravity studies. This model, if correct, suggests the existence of strong IR relevant effects which can lead to an interesting late time cosmology. We implement the IR modification directly in the effective action. We show that, upon some assumptions on initial conditions, this model describes an observationally viable background cosmology being also consistent with local gravity tests.
Gesehen am 19.10.2017